Тривимірна польова математична модель електромагнітних процесів у торцевій зоні ротора турбогенератора - Васьковський, Ю.М.; Цивінський, С.С. (Технічна електродинаміка, 2016)
Розроблено тривимірну польову математичну модель електромагнітних процесів у торцевих зонах ротора турбогенератора в несиметричних режимах його роботи, при яких частота індукованих струмів у роторі дорівнює 100 Гц, та виконано на її основі відповідні дослідження. Наведено результати моделювання – розподіли вихрових струмів і втрат у контактних зонах клинів і зубців та обґрунтовано технічні рішення щодо їхнього зменшення. Разработана трехмерная полевая математическая модель электромагнитных процессов в торцевых зонах ротора турбогенератора в несимметричных режимах его работы, при которых частота индуцированных токов в роторе равна 100 Гц. Проведены на ее основе соответствующие исследования. Приведены результаты моделирования – распределения вихревых токов и потерь в контактных зонах концевых клиньев и зубцов, обоснованы технические решения по их уменьшению. In the operation of powerful turbogenerators (TG) there are cases of damage of the end wedges and related areas of the rotor teeth. Increased of damages of these elements caused by physical processes that occur in the rotors of TG in the asynchronous and asymmetric modes. At the ends of the rotor induced currents consistently cross over from teeth to end wedges through their contact surfaces. On these surfaces, there is a large current density and local heating. The study of these phenomena can be doing only on the basis of the field mathematical models. The purpose of this paper is to develop a three-dimensional mathematical model of the electromagnetic processes in the end zones of the rotor TG in asymmetrical modes and carrying relevant studies . The results of modeling are: the distribution of eddy currents and losses in the contact zones of the end wedges and teeth, technical solutions for their decreasing.